Perception of transformational leadership behaviour among general hospital nurses in Ogun State, Nigeria. (2017) - Olu-Abiodun, Oluwatosin; Abiodun, Olumide
Abstract: Introduction: Effective nursing leadership engenders staff retention, job satisfaction, commitment, work unit climate and client satisfaction with nursing services. This study assessed the perception of transformational leadership among nurses working in general hospitals in Nigeria. Materials and methods: A cross-sectional study was conducted among 176 nurses in Ogun State, Nigeria. The independent student t -test was used to test the relationship between respondents' characteristics and leadership behaviour scores. P value was set at 0.05. Results: The average scores for 26 leadership behaviour items ranged from 3.28 to 4.21 out of a total of 5. The mean perception scores across the four nurse leadership behaviour domains ranged from 3.50 to 3.83. Nurses' level of education was related to mean score of perception of leadership behaviour (p < 0.05). Conclusion: Transformational leadership style is perceived by nurses to be utilized by Nurse Leaders. The perception of transformational leadership style depends on the work setting and nursing qualification.